Tadlis in home financing: a comparative study of Malaysia and islamic republic of Iran - Yaakub, Ezani; Mohamed Adil, Mohamed Azam; Muhamad, Mohd Dani; Ishak, Amal Hayati (2012)
The increasing number of house defect cases in Malaysia demonstrates that the issue needs to be solved. Furthermore, there are cases where the purchasers' rights are violated especially in the issue regarding compensation should there be any defects. Therefore, this study is significant for these objectives; (i) to examine thoroughly the concept of Tadlis in housing defects; ii) to analyse the concept of Khiyar al-Ayb (option of defect) in Malaysia along with comparisons with I.R. Iran, (iii) to investigate the present provisions of law enforced in Malaysia and I.R. Iran, Hence, this research investigates, analyzes and compares the practice of tadlis in home financing both in Malaysia and Islamic Republic of Iran based on four elements, namely: i. Preventive Laws and Regulations ii. Supervision authorities (private and public) iii. Judicial Board of Financial Institutions This study has mainly collected information from interview sessions with related authorities both in Malaysia and I.R. Iran. Among the authorities in Malaysia are Construction Industry Development Board, Board of Engineers, The Ministry of Housing and Urban Development and The Tribunal of Housing Defects. Among the authorities in I.R. Iran are Bank Maskan, Municipalities, The Foundation of Islamic Revolution Construction and Board of Engineers. Based on collected information regarding tad/is in Malaysia and Islamic Republic of Iran, there are some strengths and weaknesses that is worth considering to improve and add value to the current system applied in Malaysia.